Killer at large [videorecording (DVD)] : why obesity is America's greatest threat - Clinton, Bill, 1946-; Nader, Ralph; Harkin, Tom (Disinformation Company, 2009)
Uncover the causes of obesity and the unprecedented rates in which it is spreading in the United States, and learn ways that might reverse the trend that is projected to affect 75% of Americans within the next ten years.